Primary and secondary prevention of colorectal cancer in the Czech Republic - Azeem, Kateřina; Ševčíková, Jarmila; Kyselý, Zdeněk; Horáková, Dagmar; Vlčková, Jana; Kollárová, Helena (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Colorectal cancer is one of the most frequent malignancies in the Czech Republic and worldwide. Also, a high prevalence of overweight and obesity, a high proportion of smokers in the population, and one of the highest per capita alcohol consumption rates are typical for the Czech population. The role of general practitioners in the prevention of colorectal cancer is crucial. In primary prevention, the doctor should emphasise the importance of a healthy lifestyle – a balanced diet rich in fruits and vegetables, maintaining a normal body weight, adequate physical activity, and non-smoking. In secondary prevention, patients should be informed about the possibilities of colorectal cancer screening and the benefits of early detection of the disease. Participation rates of the target population for colorectal cancer screening are low. Steps leading to increased participation in colorectal cancer screening (including postal invitations) play an important role in influencing the mortality of colorectal cancer.